2021
DOI: 10.2147/idr.s317079
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M-15 Positive Escherichia coli and Klebsiella pneumoniae Outbreak in the Neonatal Intensive Care Unit of a Maternity Hospital in Ha’il, Saudi Arabia

Abstract: Objective The aim of this study was to retrospectively characterize E. coli and K. pneumoniae isolates obtained from neonates during a suspected NICU outbreak of infection in Ha’il, Saudi Arabia during a period of one month (April 2014). Methods Antibiotic susceptibility patterns, molecular characterization for antibiotic-resistant genes ( bla TEM, bla SHV, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…CRKP is a serious threat in paediatric patients, particularly newborns, due to limited therapeutic options. 26,27 This pathogen is now considered as a reservoir for virulent and resistant genes, due to the acquisition of β-lactamase (carbapenemase and ESBLs) and the recently reported colistin resistance mcr-1 encoding genes; which make it a serious threat to human and animal. [28][29][30] These data revealed for the first time that NDM carbapenemase is widely spread among CRKP, while CTX-M and SHV were the most prevalent βlactamase in same isolates in Shenzhen's children Hospital, China.…”
Section: Discussionmentioning
confidence: 99%
“…CRKP is a serious threat in paediatric patients, particularly newborns, due to limited therapeutic options. 26,27 This pathogen is now considered as a reservoir for virulent and resistant genes, due to the acquisition of β-lactamase (carbapenemase and ESBLs) and the recently reported colistin resistance mcr-1 encoding genes; which make it a serious threat to human and animal. [28][29][30] These data revealed for the first time that NDM carbapenemase is widely spread among CRKP, while CTX-M and SHV were the most prevalent βlactamase in same isolates in Shenzhen's children Hospital, China.…”
Section: Discussionmentioning
confidence: 99%
“…SAUDI ARABIA: A retrospective research of 72 (24 E. coli and 48 K. pneumoniae ) suspected Neonatal Intensive Care Unit (NICU) outbreaks in Ha’il in 2014 showed that the majority of isolates (61 of E. coli and K. pneumoniae ) were ESBL-positive, with high-level resistance to oxyimino-cephalosporins via the simultaneous production of bla CTX-M-15 and bla SHV-12 . All K. pneumoniae isolates (42) were ST14, and all E. coli isolates (19) were ST131 [ 19 ]. Records from 2016 of a medical complex in Dammam (Eastern region of Saudi Arabia) showed that the ESBL isolates comprised 50% of the 176 E. coli and 42.1% of the 148 K. pneumoniae isolates [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among carbapenem-resistant E. coli, a study from Saudi Arabia showed a 60% prevalence rate of ESBL E. coli among E. coli infections (Al-Agamy et al, 2018). Higher prevalence rates were noted in ICU patients, especially among infants, at 79.2% (Almogbel et al, 2021).…”
Section: E Colimentioning
confidence: 99%